The Gut Microbiota at Different Developmental Stages of Apis cerana Reveals Potential Probiotic Bacteria for Improving Honeybee Health - Pham Thi Lanh; Bui Thi Thuy Duong; Ha Thi Thu; Nguyen Thi Hoa; Mi Sun Yoo; Yun Sang Cho; Dong Van Quyen (Microorganisms, 2022)
Honeybees play a vital role in the ecological environment and agricultural economy. Increasing evidence shows that the gut microbiome greatly influences the host’s health. Therefore, a thorough understanding of gut bacteria composition can lead to the development of probiotics specific for each development stage of honeybees. In this study, the gut microbiota at different developmental stages (larvae, pupae, and adults) of the honeybees Apis cerana in Hanoi, Vietnam, was assessed by sequencing the V3–V4 region in the 16S rRNA gene using the Illumina Miseq platform. The results indicated that the richness and diversity of the gut microbiota varied over the investigated stages of A. cenara. All three bee groups showed relative abundance at both phylum and family levels. In larvae, Firmicutes were the most predominant (81.55%); however, they decreased significantly along with the bee development (33.7% in pupae and 10.3% in adults) in favor of Proteobacteria. In the gut of adult bees, four of five core bacteria were found, including Gilliamella apicola group (34.01%) Bifidobacterium asteroides group (10.3%), Lactobacillus Firm-4 (2%), and Lactobacillus Firm-5 (1%). In contrast, pupae and larvae lacked almost all core bacteria except G. apicola (4.13%) in pupae and Lactobacillus Firm-5 (4.04%) in larvae. This is the first report on the gut microbiota community at different developmental stages of A. cerana in Vietnam and provides potential probiotic species for beekeeping.